Pengaruh Pupuk Nitrogen dan Ethephon terhadap Pertumbuhan, Pembungaan dan Hasil Padi Lokal (Oryza sativa L. cv. Rojolele) - Diah Rachmawati; Maryani Maryani; Tri Setyaningsih (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Physiological studies on Rojolele rice were conducted after the application of nitrogen fertilizer and ethephon at different doses. Application of nitrogen fertilizer is one of the most important measurements to improve plant growth and yield of rice. Ethylene which has flowering initiate roles are induced by ethephon. The objective of this study was to analyze the effect of nitrogen fertilizer and ethephon on growth, flowering and yield of rice (Oryza sativa L. cv. Rojolele). The experiment was carried out using Complete Randomized Design with 2 factors, which each factor consisted of four levels. The first factor was doses of urea as nitrogen source 0, 50, 100 and 150 kg ha-1. The second factor was doses of ethephon 0; 100; 200 and 400 mg l-1. Measured parameters were plant height, tiller number, plant biomass, root shoot ratio, flowering time, yield and grain size. The application of nitrogen fertilizer improved the plant growth of Rojolele rice. Plant height, tiller number, plant biomass, panicle length, and number of grains increased by the increasing doses of nitrogen, but this factor did not significantly affect on grain size. Ethephon application reduced plant height and delayed flowering time. However, it simultaneously increased tillers when compared at the same N dose. Interaction between nitrogen fertilizer and ethephon gave significantly effects on the plant height and number of grains per panicle, but there were no significant effect on the rice grain size.